2014
DOI: 10.1093/eurheartj/eht495
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after alcohol septal ablation for hypertrophic obstructive cardiomyopathy: a comparison with general population

Abstract: This study suggests that in patients with HOCM and important symptoms who underwent ASA, long-term survival after the procedure did not differ significantly from that of the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 29 publications
(24 reference statements)
7
44
0
7
Order By: Relevance
“…Periprocedural mortality of ASA in this study (0.9%) was low and comparable to that of other tertiary referral centers [8,11,21,22]. No further lethal ventricular arrhythmia occurred in the three successfully resuscitated patients during follow-up suggested the prognostic significance of periprocedural cardiac arrest was limited, which agreed with the role of VF complicating acute MI [21,23,24].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Periprocedural mortality of ASA in this study (0.9%) was low and comparable to that of other tertiary referral centers [8,11,21,22]. No further lethal ventricular arrhythmia occurred in the three successfully resuscitated patients during follow-up suggested the prognostic significance of periprocedural cardiac arrest was limited, which agreed with the role of VF complicating acute MI [21,23,24].…”
Section: Discussionsupporting
confidence: 83%
“…Several studies suggested age as an independent predictor of adverse events [8,21,25,28], whereas Cox regression analysis did not identify this variable as an independent risk factor of primary or secondary end point in this study, which was in line with Veselka et al [29]. We should note that age-related adverse events mainly occurred in patients older than 60 years [8,25,28].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Поскольку с этической точки зрения невозможно сопоставле-ние ЭСА с оптимальной медикаментозной терапией у симптоматических пациентов, данное вмешательство сравнивали с «золотым стандартом» лечения этого пула больных -хирургической миэктомией (ХМ). Таким образом, данная процедура укрепилась в комплексном лечении этих пациентов [1][2][3][4].…”
Section: Introductionunclassified
“…Под септальной редукционной терапией понимают любой из методов: хирургическую миэкто-мию либо этаноловую септальную аблацию [2]. В то же время в американских рекомендациях 2011 г.…”
Section: Introductionunclassified